Miniaturized Biamperometric Detectors for Electrochemical Detection in Flowing Streams - Komendová, Martina; Metelka, Radovan; Urban, Jiří (Wiley-VCH, 2017)
Capillary electrochemical detectors with various configurations of electrodes were developed by inserting platinum multielectrodes (tetrodes) or platinum and carbon microelectrodes into the ending of capillaries. The biamperometric mode of detection, without the need of classical reference electrode, was employed in flow injection analysis of dopamine and norepinephrine selected as model samples. The influences of geometric shape of tetrodes, arrangement of electrodes and internal diameter of the capillary were studied thoroughly with respect to intensity of recorded currents. A novel pulse biamperometric technique was employed with the aim to enhance further the recorded currents of dopamine oxidation and to minimize the passivation of electrodes in mixed aqueous-organic carrier solution, which improved considerably the repeatability of measurements. Proposed low-cost microelectrode devices showed good prospects as detectors in simple and miniaturized flow systems, such as flow injection analysis and capillary high-performance liquid chromatography with monolithic columns.
Miniaturizované biamperometrické detektory pro elektrochemickou detekci v průtočných systémech
Keywords: Capillary electrochemical detectors; Microelectrodes; Tetrode; Dopamine; Norepinephrine; Biamperometry; Kapilární elektrochemické detektory; Mikroelektrody; Tetroda; Dopamin; Noradrenalin; Biamperometrie